Association between short sleep duration and body mass index in Australian Indigenous children - Deacon-Crouch, Melissa (My University, 2017)
Aim: Associations between short sleep duration and obesity and the relationship between obesity and chronic illness are well documented. Obese children are likely to become obese adults. To date, there is a paucity of information regarding sleep duration and quality for Indigenous Australian people. It may be that poor-quality, short sleep is contributing to the gap in health outcomes for Indigenous people compared with non-Indigenous adults and children. This study sought to investigate the possibility that poor sleep quality may be contributing to health outcomes for Indigenous children by exploring associations between sleep duration and body mass index (BMI). Methods: Participants included 1253 children aged 7–12 years in Wave 7 of the national Longitudinal Study of Indigenous Children survey. Interviewers asked primary carers about children’s sleep times. BMI was derived from measurements of children made by researchers. Results: Regardless of age, relative socio-economic disadvantage and level of remoteness, unhealthy weight was associated with less sleep duration than healthy weight for Indigenous children. Conclusion: The relationship between short sleep duration and BMI in Indigenous children has important implications for their future health outcomes. Both overweight conditions and short sleep are established modifiable risk factors for metabolic dysfunction and other chronic illnesses prominent in the Indigenous population. It is important to consider strategies to optimise both for Indigenous children in an attempt to help ‘close the gap’ in health outcomes and life expectancy between Indigenous and non-Indigenous people.
Keywords: Children; Health -- Obesity; Health -- Body size, BMI, Body image; Health and wellbeing; Children; Health; Body size, BMI, Body image; Obesity; Health and wellbeing